Journey of the soul: The cultural, spiritual, and personal significance of Hajj in Na'ima B. Robert's Going to Mecca - Mariwan Hasan (Universitas Merdeka Malang, 2025)
Na’ima B. Robert’s Going to Mecca, portrays the Hajj pilgrimage as a rich, multifaceted journey that transcends its role as a religious obligation to embody cultural, spiritual, and personal significance. Through the experiences of her characters, Robert illustrates how Hajj functions as a rite of passage that strengthens Muslim identity, reinforces communal bonds, and fosters deep spiritual awakening. The pilgrimage emerges as a transformative process in which characters navigate the intersection of faith, family expectations, and personal aspirations. This study explores how Robert’s narrative encapsulates the pilgrimage’s cultural role as a marker of collective belonging, its spiritual function as a journey of the soul, and its personal dimension as a catalyst for introspection and growth. By analyzing the interplay of these dimensions, the research highlights the continued relevance of Hajj as a powerful symbol of identity and renewal in contemporary Muslim experience.